Engineering chromosome region maintenance 1 fragments that bind to nuclear export signals. (14th September 2019) - Lei, Yuqin; An, Qi; Zhang, Yuqing; Luo, Ping; Luo, Youfu; Shen, Xiaofei; Jia, Da; Sun, Qingxiang
Abstract: Chromosome region maintenance 1 (CRM1) exports nuclear export signal (NES) containing cargos from nucleus to cytoplasm and plays critical roles in cancer and viral infections. Biochemical and biophysical studies on this protein were often obstructed by its low purification yield and stability. With the help of PROSS server and NES protection strategy, we successfully designed three small fragments of CRM1, each made of four HEAT repeats and capable of binding to NESs in the absence of RanGTP. One of the fragments, C7, showed dramatically improved purification yield, thermostability, mechanostability, and resistance to protease digestion. We showed by isothermal titration that the protein kinase inhibitor NES binds to C7 at 1.18 μM affinity. Direct binding to C7 by several reported CRM1 inhibitors derived from plants were verified using pull‐down assays. These fragments might be useful for the development of CRM1 inhibitors towards treatment of related diseases. The strategy applied here might help to tackle similar problems encountered in different fields.